Factors influencing the spread of local anesthetic during the transverse abdominal plane block (study on unfixed corpses) - E. K. Bespalov; D. I. Novikov; A. Yu. Zaitsev; V. A. Svetlov; A. A. Evstropova (Вестник анестезиологии и реаниматологии, 2023)
Introduction. Despite the proven clinical effectiveness of the transverse abdominal plane block (TAP block), the factors affecting the distribution of local anesthetic in the fascial case have not been fully studied, and there are no clear recommendations regarding the choice of the volume of local anesthetic taking into account anthropometry.The objective was to identify anthropometric factors influencing the choice of an adequate volume of local anesthetic for performing a TAP block.Materials and methods. In the pathology department, 40 upper and 40 lateral TAP blocks were performed in 20 corpses using ultrasound navigation. On the right side, 20 ml (block group A) of diamond green dye solution was injected, on the left side - 30 ml (block group B). The dependence of the area of distribution of the dye solution on the volume of the body, weight and height of the corpse was investigated. The analysis of the effect of damage in the execution zone on the area of dye distribution was carried out.Results. In the group B, the dye in 100 % of cases (n=18) spread to the nerve passage areas Th6 – Th9 in the upper TAP block and Th9 – L1 in the lateral TAP block. In group A, in 38.8 % of cases (n=7), the dye did not spread to the Th8-Th9 nerve passage area with the upper TAP block, as well as to the Th10 and Th12–L1 passage areas with the lateral TAP block. An inverse correlation of the growth and the dye distribution area was revealed (p < 0.01). In all unfixed corpses whose height exceeded 179 cm, the dye could not compromise all the zones of passage of nerve structures. Tissue damage in the area of the block limited the spread of the dye.Conclusion. Adequate distribution of local anesthetic depends on the patient’s height. With the height of >179 cm, 20 ml may not be enough to perform a TAP block, and <177 cm – 30 ml may be excessive.